Effect of Floating Needle Perfusion Therapy combined with Joint Mobilization on Shoulder Pain of Hemiplegia after Stroke - Xin WANG; Hu LI; Xiuyan LU (康复学报)
Objective:To observe the effect of floating needle perfusion therapy combined with joint mobilization on shoulder pain of hemiplegia after stroke. Methods: A total of 90 hemiplegia patients with shoulder pain after stroke in the department of rehabilitation medicine of Shandong Provincial Third Hospital from February to December 2019, which were divided into the control group, the floating needle group and the comprehensive group according to the random number table, with 30 cases in each group. The control group only received routine rehabilitation training, including normal limb position, prevention of secondary injury, active or auxiliary functional exercise, low-frequency electrical stimulation, and daily living ability simulation training of upper limb, etc., 25 minutes a time, once a day, five days per week, continuous treatment for four weeks. The floating needle group received floating needle perfusion therapy on the basis of the control group, when the pain in the front of the shoulder joint was obvious, the affected muscle was generally 5 cm from the distal end of the elbow joint, when the pain in the middle or back of the shoulder joint was obvious, the affected muscle was generally near the posterior lower edge of the deltoid muscle. The affected muscle was taked as the needle entry point, and the needle tip was facing the shoulder joint, after inserting into the loose connective tissue, the needle body was scanned in arc, 100 times per min, one min per group, three groups each time. After each sweep, the shoulder joint should be actively or assist to move around 10 times, the direction and range of motion should be mild pain, keeping the needle for 24 h, twice a week, continuous treatment for four weeks. The comprehensive group received shoulder joint mobilization treatment on the basis of the floating needle group, 25 min per time, once a day, five days per week. Firstly, the pain of shoulder joint was relieved by 1-2 grade manipulation, and then the adhesion was released by 3-4 grade manipulation, including separating and pulling shoulder joint along the long axis to relieve pain, sliding to release joint capsule, swinging to maintain and expand joint range of motion, taking measures to reach but not exceed the pain point, each manipulation was performed 3-4 times. Before treatment and after treatment for four weeks, the visual analogue scale (VAS) was used to assess shoulder pain, the Fugl-Meyer assessment (FMA) was used to assess upper extremity motor function, the modified Barthel index (MBI) was used to assess activities of daily living, and the goniometer was used to measure the passive range of motion of the shoulder joint.Results:Before treatment, there were no significant differences in VAS scores, FMA scores, MBI scores and PROM of the shoulder joint in three groups, with no statistically significant differences (P> 0.05). Compared with before treatment, the VAS score of the three groups after treatment for four weeks decreased significantly, while the FMA score, MBI score and PROM of the shoulder joint increased significantly, with statistically significant differences (P< 0.05). Compared with the control group, the VAS scores of the floating needle group and the comprehensive group decreased significantly, while the the FMA score, MBI score and PROM of the shoulder joint increased significantly, with statistically significant differences (P< 0.05). Compared with the floating needle group, the VAS score of the comprehensive group decreased significantly, while the FMA, MBI scores and PROM of the shoulder joint increased significantly, with statistically significant differences (P< 0.05).Conclusion:Floating needle perfusion therapy combined with joint mobilization could effectively relieve shoulder pain of hemiplegia patients after stroke, and improve the motor function of upper limb and activity of daily living, which is worthy of clinical application and promotion.